Effect of different diluents on the quality of sperm sexing cows with a gradient albumin (egg white) - Ervandi M; Susilawati T; Wahyuningsih S (Jurnal Ilmu Ternak dan Veteriner, 2013)
Damage of spermatozoa membrane in sexing procces with albumin gradient can decrease the quality of spermatozoa, thus to solve that need diluents for protect spermatozoa membrane to make good quality. The aim of this research is to know the best diluents between Andromed and CEP2 (cauda epididymal plasma) + 0% of yolk to keep the quality of Limousin Cow’s Spermatozoa from sexing procces with albumin’s gradient. Parameters measured for the quality of spermatozoa were : spermatozoa motility, spermatozoa viability, spermatozoa abnormality, spermatozoa concentration, and spermatozoa motility, membrane integrity, spermatozoa capacity, and acrosom reaction. Observation of membrane integrity using HOS (Hypoosmotic Swelling Test), observation of capacity and acrosom reaction using fluoresen CTC (Chortetracycline) dye. Result show that Andomed diluents and CEP2 + 10% yolk in top layer and bottom (X) and (Y) layer can keep the quality of Limousin Cow’s spermatozoa in sexing procces include spermatozoa motility (X 62,5%, Y 58%,) (X 56,5%, Y 55%), viability (X 91,64%, Y 91,51%) (X 89,87%, Y 93,51%, spermatozoa’s concentration (X 643 million /ml, Y518 million /ml) (X648 million/ml, Y517 million/ml), total spermatozoa are motil (X373,60 juta/ml, Y187,80 million/ml) (X 296,03 miliion/ml, Y 187,38 million/ml) , and have low abnormality (X 4,11%, Y 4,38%), (X 6,42%, Y 4,04%). Andromed diluents and CEP2 + 10% yolk can keep the integrity of spermatozoa membrane (X 87,60%, Y 80,26%) (X 79,61%, Y 81,03%), remains well and have the spermatozoa are not yet capacitation(X 87,60%, Y83,71%) (X 79,61%, Y 81,03%) remains high, spermatozoa capacity (X 9,76%, Y 9,92%) (X 13,45%, Y 8,95%), dan acrosom reaction (X 4,11%, Y 4,38%), (X 6,42%, Y 4,04%) remains low. Andromed diluents was not different (P > 0,05) from CEP2 diluents + 10% yolk in keeping the quality of Limousin Cow Spermatozoa from the sexing process with albumin’s gradient (egg white). Key Words: Semen, Andromed, CEP+10% Yolk, Albumin’s Gradient, Sexing